Coincidence point theorems for φ-ψ-contraction mappings in metric spaces involving a graph - Yolacan, E.; Kiziltunc, H.; Kir, M. (Carpathian Mathematical Publications, 2016)
Some new coupled coincidence and coupled common fixed point theorems for φ-ψ-contraction mappings are established. We have also an application to some integral system to support the results.